2020
DOI: 10.31033/ijrasb.7.5.40
|View full text |Cite
|
Sign up to set email alerts
|

Field Bio-Efficacy of “Brigade-BL” (Beauveria bassiana) an Entomopathogenic Fungi for the Management of Mealy Bugs on Thompson Seedless Grapes

Abstract: A field bio-efficacy of Brigade-BL (Beauveria bassiana) an entomopathogenic fungi was evaluated against mealy bugs (Meconellicoccus hirsutus) on Thompson Seedless grapes at National Research Centre on Grapes, Manjri, Pune during 2014-15. The experiment was conducted in RBD with five replications on foundation pruning and fruit pruning. Results obtained revealed that application of Brigade-BL @ 5.0 ml/L with two sprayings resulted in reduction of mealy bug colonies upto 67.82% in foundation pruning as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Figures in the parentheses are arcsine transformed values; the mean values with the same alphabetical superscripts are statistically non-significant as per DMRT DAT days after treatment, FORS Fish Oil Rosin Soap the present trial the spore concentration used was 2 × 10 8 cfu/ml. Kanitkar et al (2020) revealed that application of Brigade-BL (B. bassiana) at 5.0 ml/l with 2 sprayings resulted in reduction of mealy bug colonies up to 67.82 and 75.68% in foundation and fruiting pruning, respectively. Similarly, it has not resulted in any abnormality and phytotoxic effects like leaf chlorosis, tip burning, necrosis, epinasty, and rusting on grapevines and were found compatible with Buprofezin 25 SC chemical insecticide.…”
Section: T16mentioning
confidence: 99%
“…Figures in the parentheses are arcsine transformed values; the mean values with the same alphabetical superscripts are statistically non-significant as per DMRT DAT days after treatment, FORS Fish Oil Rosin Soap the present trial the spore concentration used was 2 × 10 8 cfu/ml. Kanitkar et al (2020) revealed that application of Brigade-BL (B. bassiana) at 5.0 ml/l with 2 sprayings resulted in reduction of mealy bug colonies up to 67.82 and 75.68% in foundation and fruiting pruning, respectively. Similarly, it has not resulted in any abnormality and phytotoxic effects like leaf chlorosis, tip burning, necrosis, epinasty, and rusting on grapevines and were found compatible with Buprofezin 25 SC chemical insecticide.…”
Section: T16mentioning
confidence: 99%